Factores sociales y calidad de vida en personas adultas mayores de la comunidad Inés Moreno, Calceta-Manabí - Villalva Zambrano, Nayari (2026)
Population aging has become a topic of growing social interest, as it represents significant challenges for ensuring the well-being of older adults. This study aimed to analyze social factors and quality of life among older adults in the Inés Moreno community in Calceta, Manabí. It was conducted using a quantitative, descriptive, non-experimental, and cross-sectional approach, using the WHOQOL-BREF questionnaire as a data collection instrument, administered to a sample of 40 participants. The findings indicate that most participants feel generally satisfied in aspects such as their personal relationships, social support, housing conditions, and access to health services, highlighting the importance of friendships as an element of well-being. It was observed that both enjoyment of life and meaning of life are perceived at intermediate levels, reflecting the limitations inherent in the rural context, especially in infrastructure and basic services. Social factors appear to be key determinants of older adults' quality of life, highlighting the need to promote public policies and community programs that strengthen support networks and ensure successful aging.